2019
DOI: 10.3390/cells8020156
|View full text |Cite
|
Sign up to set email alerts
|

The Modern View of B Chromosomes Under the Impact of High Scale Omics Analyses

Abstract: Supernumerary B chromosomes (Bs) are extra karyotype units in addition to A chromosomes, and are found in some fungi and thousands of animals and plant species. Bs are uniquely characterized due to their non-Mendelian inheritance, and represent one of the best examples of genomic conflict. Over the last decades, their genetic composition, function and evolution have remained an unresolved query, although a few successful attempts have been made to address these phenomena. A classical concept based on cytogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 133 publications
(204 reference statements)
1
56
0
Order By: Relevance
“…Enrichment analysis detected diverse GO terms for important biological roles such as metabolism, cell adhesions, reproduction, stimulus response, localization, morphogenesis and methylation. Genes with such functions were also reported to be located on B chromosomes in previous studies (see a comprehensive and updated list of B genes in the review by Ahmad and Martins [ 2 ] ). Among the B enriched functions, we found that most of them are involved in developmental processes, particularly morphogenesis.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Enrichment analysis detected diverse GO terms for important biological roles such as metabolism, cell adhesions, reproduction, stimulus response, localization, morphogenesis and methylation. Genes with such functions were also reported to be located on B chromosomes in previous studies (see a comprehensive and updated list of B genes in the review by Ahmad and Martins [ 2 ] ). Among the B enriched functions, we found that most of them are involved in developmental processes, particularly morphogenesis.…”
Section: Discussionmentioning
confidence: 84%
“…B chromosomes (Bs) are additional and non-essential extra chromosomes, which show non-Mendelian inheritance and lack the ability of meiotic pairing unlike the normal A chromosomes [ 1 , 2 ]. The genomic characterization of Bs has remained elusive, since the discovery of Bs [ 3 ] about 112 years ago.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…He presented a set of genes discovered in 2 species of Astyanax and in the grasshopper A. flavolineata . Furthermore, S. Ahmad reviewed a long list of previously reported B chromosome genes described in fungi, plants, insects, fish, and mammals [Ahmad and Martins, 2019]. The functional annotation demonstrates that Bs have accumulated copies of many genes involved in several important biological processes, including cell cycle control and chromosome formation.…”
Section: Genes and B Chromosome Effectsmentioning
confidence: 99%